Demographic characteristics and pregnancy outcomes in adolescents – Experience from an Australian perinatal centre. (20th June 2017) - Daniels, Samuel; Robson, Danielle; Flatley, Christopher; Kumar, Sailesh
Abstract : Background: Adolescent pregnancy is defined as pregnancy in girls aged 10–19 years and can be associated with increased risks. Aim: To investigate obstetric and perinatal outcomes in a cohort of adolescent girls from a major Australian tertiary centre. Materials and Methods: This was a nine‐year retrospective cohort study of women who birthed at the Mater Mother's Hospital (MMH) in Brisbane, Australia between 1 January 2007 and 31 December 2015. The adolescent cohort was aged <19 years and the control group was aged 20–24 years. Results: Over the study period the total study cohort comprised 8904 women. Of these, the adolescent cohort consisted of 1625 girls (18.2%) and the control group consisted of 7279 women (81.8%). Adolescents were more likely to be nulliparous, single, of Indigenous ethnicity or to have refugee status. They had higher rates of smoking, asthma, diabetes mellitus and thyroid disease. They were more likely to have an uncomplicated spontaneous vaginal delivery but were less likely to have an intact perineum and had higher rates of pre‐term delivery and low birth weight babies. There were no differences in rates of postpartum haemorrhage. Conclusions: Teenage pregnancy results in poorer obstetric and perinatal outcomes. A focus on optimising maternal health care and providing culturally appropriate antenatal and intrapartum care is imperative to improving outcomes.